2012
DOI: 10.2190/iq.32.3.e
|View full text |Cite
|
Sign up to set email alerts
|

Why Actions for Early Treatment of Febrile Illnesses in Children are Delayed by Caregivers

Abstract: The study explored why actions for early treatment of febrile illnesses in children are delayed by caregivers of children less than five years in five Local Government Areas (LGAs) of southwestern Nigeria using four indicators: caregivers' perception of illness, notion of causation and seriousness, belief in efficacy of selected pathway, and the decision making process. Seven types of febrile illnesses (yellow fever, typhoid fever, ordinary fever/malaria, hot body fever, rain fever, cold fever, and headache fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In general, febrile illnesses among children in Nigeria are presumed by clinicians to be caused by malaria, which is still very common in many parts of the country. Only if fever persists following an empiric course of anti-malarials, is typhoid then considered as a potential cause of infection [ 8 ]. In studies from central and northwest Nigeria [ 9 ], we found that S .…”
Section: Introductionmentioning
confidence: 99%
“…In general, febrile illnesses among children in Nigeria are presumed by clinicians to be caused by malaria, which is still very common in many parts of the country. Only if fever persists following an empiric course of anti-malarials, is typhoid then considered as a potential cause of infection [ 8 ]. In studies from central and northwest Nigeria [ 9 ], we found that S .…”
Section: Introductionmentioning
confidence: 99%
“…In general, in Nigeria, febrile illnesses in children are presumed to be caused by malaria. If fever persists following an empiric course of antimalarials, it is assumed to be due to "typhoid fever" but without blood culture confirmation [4].…”
mentioning
confidence: 99%